PERSEPSI DAN SIKAP MASYARAKAT TERHADAP PENGEMBANGAN NYAMPLUNG DI DESA PATUTREJO, KABUPATEN PURWOREJO (Perception and Attitude of Community towards the Development of Nyamplung in Patutrejo Village, Purworejo District) - Sanudin Sanudin, S. Hut., M. Si (Jurnal Agroforestri Indonesia, 2020)
Global awareness of the energy crisis and the environmental impacts related to fossil fuels have driven the use of alternative energy sources such as biofuels.  Nyamplung is one type of plant suitable for biofuel production.  This study aims to determine perception and attitude community towards the development of nyamplung.  The study was conducted in April - July 2018 in Patutrejo Village, Purworejo District, Central Java. Data collection was carried out by interviewing the community involved in the Self-Sufficient Village program in 2009, namely farmers, extension workers, officials in the Forestry Service Branch and officials in Perum Perhutani. The data obtained were tabulated and analyzed using a Likert Scale. The results showed that perceptions and attitudes of the community towards the development of nyamplung are as follows: First, nyamplung is suitable to be developed for environmental functions, namely as a windbreak, which protects agricultural land near the sea to remain productive; Second, nyamplung is not profitable to be developed for biofuel business because the price of nyamplung seeds is low and the processing of nyamplung seeds requires a modern machine; and Third, the development of nyamplung for biofuels does not have the support of the community. They are not willing to plant nyamplung on their own land, are not interested in processing nyamplung seeds for biofuel and are not interested in collecting and selling nyamplung seeds.